New methodology for modeling, design and implementation of RF power amplifiers - Rafael Valdivia, Guillermo (2017)
This work presents a new methodology for modeling, design and implementation of power amplifiers in different technologies. As result of comparison, a flowchart with a new methodology is proposed which can be useful for the designer to design and implement power amplifiers with low, medium and high power devices in different technologies. This paper is divided in 4 parts: The first one is an introduction to the importance of modeling and design techniques in the final implementation of power amplifiers for the modern communication systems. The second one details the modeling process for different technologies, which final result is a unified model. The third part is related with the characterization of high power transistors, with special emphasis on substrate characterization and final implementation of a power amplifier. Finally, in the fourth part, the new methodology is proposed based on the comparisons of previous procedures.